2016
DOI: 10.1001/jamaneurol.2015.3106
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits Associated With Prestroke Antiplatelet Therapy Among Patients With Acute Ischemic Stroke Treated With Intravenous Tissue Plasminogen Activator

Abstract: IMPORTANCE Intravenous tissue plasminogen activator (tPA) is known to improve outcomes in ischemic stroke; however, many patients may have been receiving antiplatelet therapy before acute ischemic stroke and could face an increased risk for bleeding when treated with tPA. OBJECTIVE To assess the risks and benefits associated with prestroke antiplatelet therapy among patients with ischemic stroke who receive intravenous tPA. DESIGN, SETTING, AND PARTICIPANTS This observational study used data from the American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 35 publications
1
39
0
Order By: Relevance
“…However, when adjusted for confounders, the independent association between pre‐existing antiplatelet therapy and unfavorable outcomes became insignificant (adjusted OR 1.09, 95% CI 0.96–1.24). Although a high level of heterogeneity was observed in the adjusted estimates ( I 2 =76.2%, P =0.006), we were able to locate the major sources of heterogeneity through subgroup analysis (Table 4), which included the 1 study that provided only data on outcome at hospital discharge 29. The pooled adjusted estimates remained similar after the exclusion of this study (OR 1.07, 95% CI 0.83–1.37).…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…However, when adjusted for confounders, the independent association between pre‐existing antiplatelet therapy and unfavorable outcomes became insignificant (adjusted OR 1.09, 95% CI 0.96–1.24). Although a high level of heterogeneity was observed in the adjusted estimates ( I 2 =76.2%, P =0.006), we were able to locate the major sources of heterogeneity through subgroup analysis (Table 4), which included the 1 study that provided only data on outcome at hospital discharge 29. The pooled adjusted estimates remained similar after the exclusion of this study (OR 1.07, 95% CI 0.83–1.37).…”
Section: Resultsmentioning
confidence: 81%
“…All studies with follow‐up patients for functional outcomes defined favorable outcome as mRS scores of either 0 to 2 or 0 to 1 on poststroke day 90, except for 1 study that recorded patient functional outcomes at hospital discharge 29. Our pooled analysis of crude ORs showed that patients taking prior antiplatelet medications tended to have lower odds of reaching favorable functional outcomes (OR 0.86, 95% CI 0.80–0.93) (Figure 2B).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations